The Berenstain Bears, no girls allowed - Berenstain, Stan, 1923-2005 (Berenstain, Stan, 1923-2005. First time books., 1986)
Annoyed that Sister Bear always beats them at baseball and other "boy" type activities, her brother and the other male cubs try to exclude her from their new club.